2012
DOI: 10.1053/j.gastro.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Vascular Endothelial Growth Factor Regulates Recruitment of Rat Liver Sinusoidal Endothelial Cell Progenitor Cells

Abstract: Background & Aims After liver injury, bone marrow-derived liver sinusoidal endothelial cell progenitor cells (BM SPCs) repopulate the sinusoid as liver sinusoidal endothelial cells (LSECs). After partial hepatectomy, BM SPCs provide hepatocyte growth factor, promote hepatocyte proliferation, and are necessary for normal liver regeneration. We examined how hepatic vascular endothelial growth factor (VEGF) regulates recruitment of BM SPC and their effects on liver injury. Methods Rats were given injections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 29 publications
7
83
0
Order By: Relevance
“…These observations correlate with more recent work in which loss of LSEC viability occurs after 24h of liver injury, but before hepatocyte necrosis, suggesting that a VEGF-regulated engraftment of BM SPC, an alternative source of HGF, may latterly stimulate hepatocyte proliferation and liver regeneration [91]. Certainly, VEGF knockdown significantly decreases partial hepatectomy-induced BM SPC proliferation and engraftment to the liver [87]. These studies suggest that loss of LSEC functionality seems to be the input signalling in the bone marrow-liver crosstalk, which will promote the release of BM SPC, regeneration of the liver, and at a very final step reconstitution of LSEC structures will occur.…”
Section: - Sinusoidal Crosstalk In Liver Regeneration and Transplantsupporting
confidence: 85%
See 1 more Smart Citation
“…These observations correlate with more recent work in which loss of LSEC viability occurs after 24h of liver injury, but before hepatocyte necrosis, suggesting that a VEGF-regulated engraftment of BM SPC, an alternative source of HGF, may latterly stimulate hepatocyte proliferation and liver regeneration [91]. Certainly, VEGF knockdown significantly decreases partial hepatectomy-induced BM SPC proliferation and engraftment to the liver [87]. These studies suggest that loss of LSEC functionality seems to be the input signalling in the bone marrow-liver crosstalk, which will promote the release of BM SPC, regeneration of the liver, and at a very final step reconstitution of LSEC structures will occur.…”
Section: - Sinusoidal Crosstalk In Liver Regeneration and Transplantsupporting
confidence: 85%
“…LSEC and HSC divide approximately 96h after partial hepatectomy, primarily due to hepatocyte-derived VEGF/angiopoietin stimulation, and proteins relying on phosphoinositide 3-kinase for their mitogenic effect, respectively [8385]. There is an evident cooperation among non-parenchymal and parenchymal cells during regeneration [86], however, the idea that bone marrow-derived endothelial sinusoidal progenitor cells (BM SPC), rich in hepatocyte growth factor (HGF), are also recruited to the site of the injury is now emerging [87, 88]. Recently, Katagiri and colleagues observed that a small representation (1–2%) of bone marrow mesenchymal stem cells, named Muse, differentiate into liver-lineage cells and repair tissue.…”
Section: - Sinusoidal Crosstalk In Liver Regeneration and Transplantmentioning
confidence: 99%
“…Further, in one study, reestablishment of LSEC fenestrae via restoration of VEGF function fully reversed portal hypertension and its secondary manifestations [8]. Finally, VEGF facilitates the recruitment of bone marrow-derived LSEC progenitor cells during liver regeneration [106]. Thus, the role of VEGF in liver injury, fibrosis, and portal hypertension, as well as its role in the recovery from these processes will require further exploration.…”
Section: Translational Implications and Future Directionsmentioning
confidence: 99%
“…In addition, VEGF regulates the recruitment of rat liver progenitor sinusoidal endothelial cells to the liver, which is a crucial step for regeneration [29]. VEGF is a large family of 5 members in mammals, namely VEGFA, VEGFB, VEGFC, VEGFD, and placental growth factor.…”
Section: Discussionmentioning
confidence: 99%